A Challenging Case of Refractory Hepatic Encephalopathy in a Postliver Retransplant Patient with Thrombosed Portal Vein: A Shunt for a Shunt. (25th February 2023) - Salama, Fady; Leyson, Anna Christina; Shah, Malay; Galuppo Monticelli, Roberto
Abstract : Hepatic encephalopathy (HE) is a frequent and serious complication of chronic liver disease. The mechanism of hepatic encephalopathy is not entirely clear. Hepatic encephalopathy is defined as brain dysfunction caused by liver insufficiency and/or portal-systemic blood shunting. It manifests as a wide spectrum of neurological or psychiatric abnormalities, ranging from subclinical alterations, detectable only by neuropsychological or neurophysiological assessment, to coma. Liver transplant (LT) is the definitive treatment for refractory hepatic encephalopathy. In this case, we present a challenging case of refractory hepatic encephalopathy in a postliver transplant patient with portal vein thrombosis and a splenorenal shunt treated with a novel technique to address his complex anatomy.